2016
DOI: 10.5812/archcid.33904
|View full text |Cite
|
Sign up to set email alerts
|

Delay in Post-Exposure Prophylaxis and Associated Factors Among People Bitten by Animals in the Northeast of Iran, 2015

Abstract: Background: Despite the importance of post-exposure prophylaxis (PEP), studies conducted in Iran on PEP showed different findings and it is not well documented yet. Objectives:The current study aimed to evaluate the delayed time of PEP and associated factors in bitten people. Materials and Methods: This cross-sectional study was conducted on 397 subjects of animal bites in Khalilabad County, Northeast of Iran, from March 2012 to March 2013. The census method was employed to use the data on animal bites recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…There was also a significant correlation between delayed PEP and type of Season of bite. In concordance with a similar study [ 5 ]. According to our finding, a significant relationship was observed between delayed PEP and number of injuries.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…There was also a significant correlation between delayed PEP and type of Season of bite. In concordance with a similar study [ 5 ]. According to our finding, a significant relationship was observed between delayed PEP and number of injuries.…”
Section: Discussionsupporting
confidence: 94%
“…Another study carried out in one of the provinces in west Iran (Hamadan province) showed that 425 cases of animal bites were reported from February 2011 to February 2012 [ 4 ]. Furthermore, the study by Khazaei et al ., [ 5 ]. Another study in Quechan city in 2013 reported an incidence of 442 animal bites per 100 000 people [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is different to the finding of Khazaei in the study conducted in Iran where the delay of PEP was quite the same in rural 7% and urban 5.7%. [17] On other hand, our finding corroborates with what found in the study conducted in Kenya. [18] Considering the possession of medical insurance, dog bites victims who did not owned a medical insurance were 5.3(95% CI, 2.3-12.1) times higher to delay for rabies PEP, this could be attributed to the fear of the cost of PEP.…”
Section: Discussionsupporting
confidence: 91%